2023
DOI: 10.1111/1365-2664.14522
|View full text |Cite
|
Sign up to set email alerts
|

Culling‐induced perturbation of social networks of wild geese reinforces rather than disrupts associations among survivors

Beatrice C. Downing,
Matthew J. Silk,
Richard J. Delahay
et al.

Abstract: Wildlife populations may be the subject of management interventions for disease control that can have unintended, counterproductive effects. Social structure exerts a strong influence over infectious disease transmission in addition to other characteristics of populations such as size and density that are the primary target for disease control. Social network approaches have been widely used to understand disease transmission in wildlife but rarely in the context of perturbations, such as culling, despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Effects of lethal control on wolves and their attacks may then be evaluated through promising methods such as animal social network analysis, which was applied to study the resilience of other social animals to human-induced removals (e.g. Downing et al, 2023;Goldenberg et al, 2016).…”
Section: Perspectivesmentioning
confidence: 99%
“…Effects of lethal control on wolves and their attacks may then be evaluated through promising methods such as animal social network analysis, which was applied to study the resilience of other social animals to human-induced removals (e.g. Downing et al, 2023;Goldenberg et al, 2016).…”
Section: Perspectivesmentioning
confidence: 99%
“…In particular, epidemic risk strongly depends on the population’s demographics and connectedness as well as between-individual variation in social interactions, among other factors 16 . Previous studies have shown that perturbations that alter a group’s social structure 15 can slow the spread of infections in wild animals 17,18 , or speed up pathogen spread if the group becomes more densely connected 19 . Natural disasters constitute large ecological perturbations and given that climate change is predicted to increase the frequency and severity of extreme weather events 20 , it is imperative that we evaluate the long-term effects of such disasters on epidemic risk in both animal and human populations.…”
Section: Main Textmentioning
confidence: 99%